2008
DOI: 10.1159/000121382
|View full text |Cite
|
Sign up to set email alerts
|

Resting Tremor Secondary to a Pineal Cyst: Case Report and Review of the Literature

Abstract: Background: Patients with pineal lesions typically present with the classical signs of increased intracranial pressure (headache, nausea, vomiting) and/or Parinaud’s syndrome. Rare symptomatology of secondary parkinsonism attributed to pineal lesions has been previously reported in the literature. We describe an unusual case of a pineal cyst in a patient with the presenting sign of a resting tremor. Case Description: We report an 18-year-old Caucasian female who presented with a 1-month history of a new-onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In our practice, we would limit the signs and symptoms that may be confidently attributed to a pineal cyst to Parinaud syndrome, focal cranial neuropathies, or signs and symptoms due to hydrocephalus resulting from aqueductal compression. There have been reports of pineal cysts associated with various symptoms and syndromes, including resting tremor, 43 retinoblastoma, 27,53,57 polycystic kidney disease, 1 Aicardi syndrome, 2,44 precocious puberty, 14,21,32 and even schizophrenia. 13 We doubt there are any causal associations between pineal cysts and these various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In our practice, we would limit the signs and symptoms that may be confidently attributed to a pineal cyst to Parinaud syndrome, focal cranial neuropathies, or signs and symptoms due to hydrocephalus resulting from aqueductal compression. There have been reports of pineal cysts associated with various symptoms and syndromes, including resting tremor, 43 retinoblastoma, 27,53,57 polycystic kidney disease, 1 Aicardi syndrome, 2,44 precocious puberty, 14,21,32 and even schizophrenia. 13 We doubt there are any causal associations between pineal cysts and these various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…4,14,26,43,46 Pineal apoplexy (caused by hemorrhage), Parinaud's phenomenon (caused by compression of the superior colliculus), parkinsonian symptoms, choroid plexus papilloma formation, aseptic meningitis (due to cyst rupture), pseudo-precocious puberty (due to immaturity of the hypothalamic-gonadal axis), and diabetes insipidus are less frequent yet reported symptoms. 21,26,30,31,37,38,41 There is also thought to be a hormonal and melatonin imbalance in most of these patients with headaches. In our patient population, we found that headache was one of the most common indications for undergoing MRI, with a total of 16 patients (20%) presenting with this symptom.…”
Section: Discussionmentioning
confidence: 99%
“…In pineal cysts, headache and other symptoms of raised ICP are common. Morgan et al42 present a young female with new-onset resting tremor secondary to a pineal cyst. A possible explanation for the tremor could be the disturbance of the microvasculature surrounding the nigro-striatal-pallidal system.…”
Section: Cysts Vascular Malformations and Tumorsmentioning
confidence: 99%